2018
DOI: 10.1371/journal.pone.0209319
|View full text |Cite
|
Sign up to set email alerts
|

Assessing construct validity of the Grit-S in Chinese employees

Abstract: This research examined the psychometric properties and construct validity of the Short Grit Scale (Grit-S) in Chinese insurance employees (N = 2,363; 37% males; mean age = 35.14). Exploratory factor analysis and confirmatory factor analysis (CFA) were used to determine the factor structure of the Grit-S. The resulting model was tested by multi-group CFA for the factorial invariance of the Grit-S across genders and age groups. Results showed that the Grit-S could be best explained by a two-factor model containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 44 publications
8
38
0
2
Order By: Relevance
“…Following the work of , the Grit-S has been formally translated into Japanese (Nishikawa et al, 2015), Turkish (Sarıçam et al, 2015), Filipino (Datu et al, 2016), German (Schmidt et al, 2017), Polish (Wyszyńska et al, 2017), Spanish (Arco-Tirado et al, 2018), and Chinese (Wang et al, 2017;Li et al, 2018;Zhong et al, 2018). Overall, cross-sectional data show that each version of the Grit-S has acceptable psychometric properties and that each translation resembles the English-speaking version (see Table 1).…”
Section: The Grit Scale and Its Short Versionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the work of , the Grit-S has been formally translated into Japanese (Nishikawa et al, 2015), Turkish (Sarıçam et al, 2015), Filipino (Datu et al, 2016), German (Schmidt et al, 2017), Polish (Wyszyńska et al, 2017), Spanish (Arco-Tirado et al, 2018), and Chinese (Wang et al, 2017;Li et al, 2018;Zhong et al, 2018). Overall, cross-sectional data show that each version of the Grit-S has acceptable psychometric properties and that each translation resembles the English-speaking version (see Table 1).…”
Section: The Grit Scale and Its Short Versionmentioning
confidence: 99%
“…That is, the establishment of MI is a prerequisite for meaningful comparisons across groups (e.g., male vs. female) (Chen, 2008). Previous studies (Datu et al, 2016;Schmidt et al, 2017;Zhong et al, 2018) have discussed the MI of the Grit-S scores for gender, educational levels, and age groups. For example, Zhong et al (2018) showed that the self-report measure of Grit-S has strict MI across gender and age in Chinese insurance employees.…”
Section: Measurement Invariance Of the Grit-smentioning
confidence: 99%
See 3 more Smart Citations